2016
DOI: 10.1136/annrheumdis-2016-eular.2608
|View full text |Cite
|
Sign up to set email alerts
|

AB0248 Circulating Cell Free DNA; A Marker To Predict The Therapeutic Response for Biological Dmards in Rheumatoid Arthritis

Abstract: BackgroundDNA is fragmented and released into blood circulation as results of damage or death of cells from peripheral bloods as well as organ tissues, and circulating cell-free DNA (ccfDNA) has been recognized as biomarkers of several medical conditions [1]. In patients with rheumatoid arthritis (RA), serum concentration of ccfDNA has been reported to be elevated [2], however, the relation between ccfDNA and the pathogenesis of RA remains unclear.ObjectivesTo evaluate the correlation between ccfDNA in plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It also tightly participated in immune responses in physiological conditions and lead to sterile inflammation in pathological conditions [ 2 , 3 ]. Specifically, in rheumatoid arthritis (RA) patients, the levels of cfDNA in synovial fluid (SF) and peripheral blood were highly elevated [ 4 ]. Genetic sequencing also identified that cfDNA in SF of RA was rich in hypomethylated cytosine-phosphate- guanosine (CpG) and could cause severe inflammation both in vitro and in vivo through upregulation of TNF-α expression [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also tightly participated in immune responses in physiological conditions and lead to sterile inflammation in pathological conditions [ 2 , 3 ]. Specifically, in rheumatoid arthritis (RA) patients, the levels of cfDNA in synovial fluid (SF) and peripheral blood were highly elevated [ 4 ]. Genetic sequencing also identified that cfDNA in SF of RA was rich in hypomethylated cytosine-phosphate- guanosine (CpG) and could cause severe inflammation both in vitro and in vivo through upregulation of TNF-α expression [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%